Game for Children with Special Needs - Suhono, Kwee Andreas Setiawan (SISFORMA, 2014)
In this paper, the writer discussed how to use media game which can cure someone affected with autism. Autism itself is a disorder that affects the brain, so that patients have a difficulty to communicate and relate to others. There are several factors that cause the emergence of diseases such as autism, that is, genetic factors, psychological factors, as well as food poisoning during pregnancy. In this case, the writer interviewed one of the teachers at the center of therapist in order to find out how to cure autism by using media game. The writer expected that by using the media game, people can recover from autism.